A 2D beam‐column joint macro‐element for the nonlinear analysis of RC frames. (4th November 2020) - Pantò, Bartolomeo; Caddemi, Salvatore; Caliò, Ivo; Spacone, Enrico
Abstract: Recent earthquakes have shown that the seismic behavior of noncode‐conforming reinforced concrete buildings are in several cases strongly affected by the nonlinear response and possible failure of the beam‐column joints. Beam‐column joint inelasticity is typically due to either shear cracking and failure of the central concrete panel or bond‐slip of the longitudinal steel bars. This paper proposes a new Joint with Hinges macro‐element capable of simulating the most important sources of nonlinearities in the joints. It consists of a quadrilateral central panel whose rigid edges are connected to the beams' and columns' end nodes through nonlinear finite‐length interfaces that represent the plastic hinge zones. The central panel deforms in shear only. The joint macro‐element accounts for the nonlinear shear response of the central panel, for the bond‐slip of the longitudinal rebars crossing the joint and for the nonlinear shear and flexural behavior of the plastic hinge zones of the beams and columns connected to the joint. The resulting model of the reinforced concrete frame is the assembly of nonlinear Joint with Hinges macro‐elements connected by elastic frame elements. The proposed formulation is applied in this paper to plane frames. Validation studies with results from available experimental tests on beam‐column joint subassemblages show the proposed model capability to predict the hysteretic responses and the failure mechanisms of connections with unreinforced joints and different beam reinforcement ratios.